'I don't know nothing about that': How "learning costs" undermine COVID-related efforts to make SNAP and WIC more accessible. Issue 10 (November 2022) - Barnes, Carolyn; Riel, Virginia
Scholars have focused on administrative burden or the costs of claiming public benefits. Learning, psychological, and compliance costs can discourage program participation and benefit redemption. Using 60 in-depth qualitative interviews with participants of the SNAP and WIC programs, we offer thick descriptions of how beneficiaries experience compliance, learning, and redemption costs—a subset of learning costs regarding how to redeem benefits—amidst COVID-19 policy changes. Although policy changes were poised to reduce compliance costs and ease conditions that create redemption costs in each program, the learning costs of policy changes prevented many program participants from experiencing the benefits of these policy transformations.